Women and football - Green, L.
Football in Britain is irrevocably linked to notions of masculinity. It is still widely regarded as a &quotmans game" in which women are seen as marginal, both as spectators or as players. However this has recently begun to change. The article deals with stereotypes of gender and sports, the origians of the modern game, the situationin women's football, the woman player, women as fan and recent developments.